Dialogismo e ironia na obra A mulher que escreveu a Bíblia, de Moacyr Scliar - Figueirêdo , Fernanda Medeiros de (2014)
This Work expatiates about the dialogical relations and the irony that take place amongst Literature and the Jewish-Christian universe presented in Moacyr Scliar‘s novel ―A Mulher Que Escreveu a Bíblia‖ (The Woman Who Wrote the Bible), also considering the author‘s own tradition and religion as an element in his fiction. It is important to note that Scliar directly mentions Harold Bloom‘s ―The Book of J‖, which argues that a woman could have written the Pentateuch, or the Torah, according to the Jewish tradition. From such reference, Moacyr Scliar writes about how this woman could have lived and written such books, thus carnivalyzing the religious canon, and making a parody of Bloom‗s literary critics. Given that, it becomes necessary to evaluate the intrinsic link that unites literary narrative and theological ways, recognizing the Bible as a literary piece composed by complex plots and intense characters. Such bias generates a construction of parody presented by not only our study object, but also by the text to which it makes reference, that is, the Tanakh. We base this analysis on the theoretical material from Mikhail Bakhtin, Gerárd Genette, Beth Brait, Miles, Hutcheon, amongst others, concerning concepts of enunciation, dialogism , carnivalization, parody, polyphony, and humor of a deity who creates as well as destroys, in order to clarify the discourses formation and the intention of its organization in the presented narratives, fact that shows us the Jewish feature of laughing at its own people and, consequently, at its own god always to appear in Scliar‗s pieces, giving emphasis to aspects of literality, such as the irony, for example, that plays important role in the plot as an element of subversion and transgression, by bringing up anti-heroes and confrontation between controversial themes, such as erudition and vulgarity, sacred and profane, sublime and ridiculous, sanctity and sexuality, and also the ever subversion related to the female figure. By the way, the woman is taken, in this research, out of analyzing the mentioned pieces, as an essential character to the development of actions that directly face the divine fatalism. Ironically, Scliar‗s female narrator, as well as Bloom‗s ―J― do not take part on the religious circle that would later establish their texts (the Bible). The discursive figures spoken by these women enunciations bring to surface what exists beyond the discourse decoyed by the Christian myth, the transcendence of voices and the relations that unite texts, cultures, and different societies.